Green Marketing: Theory, Practice, and Strategies - Kishore Kumar, P.; Anand, Byram (Indian Journal of Marketing, 2013)
Drastic climatic changes and global warming at alarming levels are the important issues faced by mankind in today’s world. The knowledge of green marketing is helpful for business organizations, consumers and government in addressing the above-mentioned problems. The present book review on "Green Marketing: Theory, Practice, and Strategies" is useful for academicians, consultants and businessmen. This insightful new book provides a thorough introduction to the emerging field of green marketing management, including a useful exploration of the integral relationships among marketing strategy and action, macroeconomic sectors, and the environment. Book: Green Marketing: Theory, Practice, and Strategies Author: Robert Dahlstrom Publisher: CENGAGE Learning Edition: First India Edition ISBN: 9788131514597 Price: INR 250 Pages: 285 Binding: Paperback